The labour market at the time of the pandemic: the most in-demand professions - Riva, Luca (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The outbreak of the pandemic caused by Covid-19 has undoubtedly changed many of the daily dynamics to which we are accustomed, first and foremost those of a work-related nature. Consequently, in the post-pandemic scenario, it is useful to understand where we are heading and what the work of the future will be like. For this reason, I tried to put some questions to some experts in the field, organising a sort of virtual round table in which Dr Alessandro Capezzuoli, Dr Massimiliano Franceschetti and Dr Andrea Fioni participated.